2021
DOI: 10.1007/s40620-021-01136-5
|View full text |Cite
|
Sign up to set email alerts
|

The frail world of haemodialysis patients in the COVID-19 pandemic era: a systematic scoping review

Abstract: Background Patients undergoing in-centre haemodialysis (HD) are particularly exposed to the dire consequences of COVID-19. The present systematic scoping review aims to identify the extent, range, and nature of articles related to COVID-19 and maintenance HD: it reports specifically the prevalence of the COVID-19 pandemic in the HD population, implementation of strategies for the prevention, mitigation and containment of the COVID-19 pandemic in HD centres, demographic and clinical characteristics, and outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 149 publications
(613 reference statements)
2
27
0
Order By: Relevance
“…Lack of transportation, staff shortages and possibly personal fear or symptoms may have contributed to missed treatments in up to half of the surveyed facilities in Africa, Latin America, Middle East, South East Asia and South Asia 43 . Mortality among infected and hospitalized patients receiving dialysis exceeded 50% in most regions of the world 45 . The pivot to home modalities was not feasible in many environments that were already strained.…”
Section: Challenges and Opportunities Of Covid-19mentioning
confidence: 99%
“…Lack of transportation, staff shortages and possibly personal fear or symptoms may have contributed to missed treatments in up to half of the surveyed facilities in Africa, Latin America, Middle East, South East Asia and South Asia 43 . Mortality among infected and hospitalized patients receiving dialysis exceeded 50% in most regions of the world 45 . The pivot to home modalities was not feasible in many environments that were already strained.…”
Section: Challenges and Opportunities Of Covid-19mentioning
confidence: 99%
“…In addition, these patients present a high case fatality rate of over 20%( 6 ) which is more than 40% in hospitalized patients. ( 5 ) These rates are much higher than those reported in the general population. ( 2 , 3 )…”
Section: Introductionmentioning
confidence: 78%
“…A recent study( 5 ) reported that the global prevalence of COVID-19 in patients on dialysis varies between 0% and 37%, with a hospitalization rate of between 35% and 88%, with admissions to intensive care units ranging from 2% to 70%. In addition, these patients present a high case fatality rate of over 20%( 6 ) which is more than 40% in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…Their impaired immunity and high burden of comorbid diseases puts them at increased risk of death and severe complications from COVID-19. [1][2][3][4][5][6] To reduce transmission of COVID-19, public health agencies quickly mandated physical distancing and self-isolation measures 7 . However, patients receiving in-center hemodialysis cannot self-isolate: uniquely, they must come to the center three times weekly for life-saving treatments which can last several hours 8 , resulting in unavoidable and regular exposure to health-care workers and other patients.…”
Section: Introductionmentioning
confidence: 99%